2020
DOI: 10.6061/clinics/2020/e1771
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity among women of low socioeconomic status living with HIV in two major cities of Brazil and Mozambique: A cross-sectional comparative study

Abstract: OBJECTIVES: Physical activity (PA) may reduce cardiovascular risk and preserve functional capacity of people living with human immunodeficiency virus (HIV). However, only limited research objectively measured PA in patients with low socioeconomic status (SES) in low-income countries, particularly in South America and sub-Saharan Africa. This study compared the PA assessed by accelerometers in women of low SES living with HIV under common antiretroviral therapy (cART) from two major cities in Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Table 1 describes the characteristics of the included articles. Among the 41 included articles, 35 (85%) were research studies involving primary data collection [ 21 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] one (2%) was a secondary analysis [ 68 ], three (7%) were systematic reviews [ 69 , 70 , 71 ], and two (5%) were narrative reviews [ 22 , 72 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 describes the characteristics of the included articles. Among the 41 included articles, 35 (85%) were research studies involving primary data collection [ 21 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] one (2%) was a secondary analysis [ 68 ], three (7%) were systematic reviews [ 69 , 70 , 71 ], and two (5%) were narrative reviews [ 22 , 72 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Study Design: Among the 35 studies involving primary data collection, 23 (66%) were quantitative [ 34 , 35 , 37 , 38 , 40 , 42 , 44 , 45 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 57 , 59 , 61 , 62 , 63 , 64 , 65 , 66 ], eight (23%) qualitative [ 21 , 36 , 39 , 41 , 47 , 55 , 56 , 58 ], and four (11%) mixed method studies [ 43 , 46 , 60 , 67 ]. Among the 23 quantitative studies, 18 (78%) studies were cross-sectional [ 34 , 37 , 38 , 40 , 42 , 44 , 45 , 48 , 49 , 50 , 52 , 53 , 54 , 59 , 62 , 63 , 64 , 66 ], two (9%) cohort studi...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to consider other factors that determine the usual practice of activity, such as environmental, sociodemographic, biological, psychological, cognitive, and sociocultural, among others [ 66 ]. For example, Mangona et al [ 67 ] demonstrated that high levels of physical activity in adult women living with HIV and undergoing ART was associated with cultural and survival factors, and not only with the pathological and physical determinants of the disease.…”
Section: Discussionmentioning
confidence: 99%